Influence of the precursor salts in the synthesis of CaSnO3 by the polymeric precursor method - Alves, Mary C. F.; Souza, Soraia C.; Lima, S. J. G.; Longo, Elson [UNESP]; Souza, A. G.; Santos, Ieda M. G. (Springer, 2007)
CaSnO3 was synthesized by the polymeric precursor method, using different precursor salts as (CH3COO)(2)Ca. H2O, Ca(NO3)(2). 4H(2)O, CaCl2. 2H(2)O and CaCO3, leading to different results. Powder precursor was characterized using thermal analysis. Depending on the precursor different thermal behaviors were obtained. Results also indicate the formation of carbonates, confirmed by IR spectra. After calcination and characterization by XRD, the formation of perovskite as single phase was only identified when calcium acetate was used as precursor. For other precursors, tin oxide was observed as secondary phase.
Keywords: Pechini method; perovskite; stannate; thermal analysis